Prevention of budget leakage through law enforcement in the tax sector in Kendari City - Tasmir; Ahmad Rustan; Rudi Iskandar Ichlas; Wahyudi Umar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Research discussing the prevention of budget leakage through law enforcement in the tax sector is an effort to overcome the problem of budget leakage which is one of the main problems in the country's financial sector. The urgency of this research is to minimize state financial losses due to budget leakage and strengthen the integrity of the tax sector in Kendari City. To achieve the expected goals, researchers will adapt research procedures with mixed methods using several data collection techniques such as interviews, questionnaires, literature studies, and conducting focus group discussions (FGDs). In conducting this research, researchers must also pay attention to ethical aspects of research, such as data privacy and security, and maintain academic integrity. This study aims to identify the factors that cause budget leakage, as well as to evaluate the effectiveness of law enforcement in preventing budget leakage in the tax sector. Thus, this study is expected to provide appropriate recommendations to overcome the problem of budget leakage that occurs in the tax sector in Kendari City. The results of this study are expected to be policy recommendations that can help improve the effectiveness of law enforcement and prevent budget leakage in the tax sector in Kendari City. In addition, this research can also contribute to the development of science, especially in the fields of law and public finance.